2018
DOI: 10.3389/fcvm.2017.00086
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Consequences of Defective Efferocytosis in Atherosclerosis

Abstract: Efficient clearance of apoptotic cells, termed efferocytosis, critically regulates normal homeostasis whereas defective uptake of apoptotic cells results in chronic and non-resolving inflammatory diseases, such as advanced atherosclerosis. Monocyte-derived macrophages recruited into developing atherosclerotic lesions initially display efficient efferocytosis and temper inflammatory responses, processes that restrict plaque progression. However, during the course of plaque development, macrophages undergo cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(200 citation statements)
references
References 119 publications
(127 reference statements)
5
173
0
2
Order By: Relevance
“…Besides PTX3, our study demonstrated that other molecules with anti-in ammatory properties are present in the male EC secretome. Speci cally, it also contains signi cant levels of calreticulin, one of the most characterized eat-me signals [58,59]. In accordance with our data in PTX3-silenced male ECs, decreased levels of calreticulin have been associated to an impaired efferocytosis [60].…”
Section: Discussionsupporting
confidence: 90%
“…Besides PTX3, our study demonstrated that other molecules with anti-in ammatory properties are present in the male EC secretome. Speci cally, it also contains signi cant levels of calreticulin, one of the most characterized eat-me signals [58,59]. In accordance with our data in PTX3-silenced male ECs, decreased levels of calreticulin have been associated to an impaired efferocytosis [60].…”
Section: Discussionsupporting
confidence: 90%
“…Widespread phagocytosis of modified lipoproteins and apoptotic cells by macrophages plays a complex role in the pathogenesis of atherosclerosis. This process can have either pro‐ and anti‐atherogenic effects through context‐dependent activation or resolution of inflammation, respectively 42,43 . To assess the effect of L13a deficiency on the phagocytic activity of macrophages, we performed phagocytosis assays with BMDM using Zymosan as a substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Specific populations of innate immune effector macrophages take up apoptotic cells in particular tissues, known as efferocytosis, which prevents apoptotic cells from being necrotic or pro-inflammatory [138]. The impaired ability of macrophage efferocytosis would enhance atherogenesis [139][140][141] and atherosclerotic plaque instability [142][143][144]. For example, interferon regulatory factor 5 (IRF5) transcription factor enhances vulnerable plaque formation in hyperlipidemic apolipoprotein E-deficient (ApoE −/− ) mice through the induction of pro-inflammatory CD11c + macrophages within atherosclerotic lesions and increasing the expansion of the necrotic core by inhibiting macrophage efferocytosis [142].…”
Section: Macrophagesmentioning
confidence: 99%